Invitation as a Panelist Wacana Seni 'Art Without Borders — How Co-Creation Between Disciplines Sparks Innovation' - Mohamad Faizuan, Mat (AP Gallery & National Art Gallery of Malaysia, 2025)
Art Without Borders — How Co-Creation Between Disciplines Sparks Innovation